Fireside corrosion behavior of thermally sprayed coatings for waste-to-energy power plant applications - Usman, Ahmad; Arrom, Luis Isern; Nicholls, John R.; Cordero, Mario; Syed, Adnan U. (Springer, 2025)
This study investigates the fireside corrosion behavior of four (Ni-22Cr, Ni-25Cr, Co-25Cr, and NiCo-25Cr) coatings, which were applied using twin wire arc spray technique and subjected to simulated waste-burning environments (a gas composition containing HCl, SO2, CO2, N2, H2O, balance N2, plus a salt deposit of 50wt.% KCl + 50wt.% K2SO4). The coatings deposited on a conventional base steel alloy (E−250) were tested under these conditions at 550 °C for 500 h in a laboratory-scale atmosphere controlled furnace. After the fireside exposure, the samples were studied using optical microscopy, SEM-EDX, and XRD to deduce coatings performance and possible corrosion mechanisms. The results indicated that all coatings, except Ni-22Cr, outperformed the E−250 steel. The Ni-22Cr and NiCo-25Cr coatings showed similar pitting corrosion behavior with more prominent corrosion pits on Ni-22Cr coating’s surface. The Co-25Cr coating showed slightly improved performance to the above two coatings, which can be attributed to the ability of Co to resist corrosion attack under these conditions. Overall, the Ni-25Cr coating composition was conclusively found to be most effective.
Keywords: 40 Engineering; Materials Engineering; 4017 Mechanical Engineering; Materials; Coatings; Coating; Corrosion; Metals and Alloys; Steel, Light Metal